Canting angle dependence of single-chain magnet behaviour in chirality-introduced antiferromagnetic chains of acetate-bridged manganese(iii) salen-type complexes. Issue 46 (16th November 2020) - Huang, Po-Jung; Miyasaka, Hitoshi
Abstract : An acetate-bridged Mn(iii ) salen-type alternating chain exhibits slow relaxation of the magnetization categolized to single-chain magnet behavior. The canting motif of the Jahn–Teller axis on the Mn(iii ) center is the key to obtain this behavior. Abstract : Canted antiferromagnetism (AFM) is considered an effective tool for designing single-chain magnets (SCMs) in homometallic chain systems. The family of manganese(iii ) (Mn III ) salen-type Schiff-base complexes is an outstanding building-unit candidate for designing SCMs because such complexes possess relatively large uniaxial magnetic anisotropy in the out-of-plane direction. However, SCM behaviour in simple alternating chains based on monomeric Mn III salen-type complexes has not been studied extensively. Herein, we report the SCM behaviour of canted AFM in an alternating chain of an acetate-bridged Mn III salen-type complex.